2020
DOI: 10.1002/cbin.11291
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1/miR‐193a‐3p/SOX5 axis regulates cartilage matrix degradation in human osteoarthritis

Abstract: Long non‐coding RNAs (lncRNAs) were reported to be involved in the progression of osteoarthritis (OA). The aim of this work was to explore the functional role of lncRNA nuclear‐enriched abundant transcript 1 (NEAT1) in OA. Reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR) was employed to analyze the expression of microRNA (miR‐193a)‐3p, NEAT1, and sex‐determining region Y‐box protein 5 (SOX5), as well as the levels of pro‐inflammatory cytokines interleukin‐6 (IL‐6), IL‐1β, tumor necrosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…We found high correlation between osteoarthritis and sciatica, fibromyalgia, headaches, and other back pain phenotypes, where the highest correlation is with spine osteoarthritis (genetic correlation [rg] = 0.61, 0.87, 0.39, and 0.79, respectively). SOX5 , one of the new signals, has been previously reported to be upregulated in human osteoarthritis cartilage ( Liu et al., 2020 ) and has been associated with back pain and with lumbar intervertebral disc degeneration ( Suri et al., 2018 ). These findings are supported by animal model data, in which inactivation of SOX5 leads to defects in skeletogenesis such as in cartilage development, the notochord, and intervertebral discs in mice ( Smits and Lefebvre, 2003 ; Smits et al., 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found high correlation between osteoarthritis and sciatica, fibromyalgia, headaches, and other back pain phenotypes, where the highest correlation is with spine osteoarthritis (genetic correlation [rg] = 0.61, 0.87, 0.39, and 0.79, respectively). SOX5 , one of the new signals, has been previously reported to be upregulated in human osteoarthritis cartilage ( Liu et al., 2020 ) and has been associated with back pain and with lumbar intervertebral disc degeneration ( Suri et al., 2018 ). These findings are supported by animal model data, in which inactivation of SOX5 leads to defects in skeletogenesis such as in cartilage development, the notochord, and intervertebral discs in mice ( Smits and Lefebvre, 2003 ; Smits et al., 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sox5 is expressed in numerous human tissues, including the testis, liver, lung, fetal brain and heart (26). Liu et al (27) demonstrated that overexpression of Sox5 can promote inflammatory responses and reverse microRNA-193a-3p mimic-mediated decrease in chondrocyte apoptosis in human osteoarthritis. However, studies have demonstrated that inhibiting Sox5 can promote apoptosis in rheumatoid arthritis and lung cancer (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…2 and S 3 ), indicating that miR-193b-3p not only reduces the production of inflammatory factors but also blocks the STAT3 and NF-κB pathways, which are two important pathways that affect the inflammatory response in psoriasis pathogenesis [ 36 , 37 ]. Interestingly, there is evidence showing that miR-193a-3p, which is a sister microRNA of miR-193b-3p and shares similar mature sequences as that of miR-193b-3p (Table S2 ), also plays crucial roles in regulating the cellular inflammation through downregulation of inflammatory factors, including IL-1β, TNF-α, and NF-κB [ 38 , 39 ]. In fact, our parallel experimental results confirmed that miR-193a-3p has functions similar to that of miR-193b-3p in HaCaT cells (Fig.…”
Section: Discussionmentioning
confidence: 99%